The Use of Pedagogical Innovations in the Lesson, The Organization of Independent Work of the Student (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the use of pedagogical innovations in the classroom when organizing student independent work. The signs, tasks, types and methods of independent work of schoolchildren are also analyzed. In the process of writing the article, such “new pedagogical technologies” were revealed as: video essay; abstract analysis and abstract review; technology of project activities; case technologies and it was revealed that innovative pedagogical technologies for organizing independent work of school students require high-quality educational and methodological materials, free access to the information world of the Internet, a specific list of basic and additional literature, and systematic control.